Bonded in death - Robb, J. D., 1950- (New York : St Martins Press, 2025)
Lieutenant Eve Dallas investigates the mysterious murder of an elderly man linked to the Urban Wars while being targeted by a vengeful killer.
Keywords: Dallas, Eve -- (Fictitious character) -- Fiction; Policewomen -- Fiction; Murder -- Investigation -- Fiction; Detective and mystery fiction